2018
DOI: 10.1371/journal.pone.0195249
|View full text |Cite
|
Sign up to set email alerts
|

Low linolenic and linoleic acid consumption are associated with chronic kidney disease in patients with type 2 diabetes

Abstract: AimThis cross-sectional study aimed to assess the association of the fat content in the diet with Diabetic Kidney Disease (DKD) in patients with type 2 diabetes.MethodologyPatients from the Diabetes research clinic at Hospital de Clínicas de Porto Alegre (Brazil) were consecutively recruited. The inclusion criterion was the diagnosis of type 2 diabetes. The exclusion criteria were as follows: body mass index >40 kg/m2, heart failure, gastroparesis, diabetic diarrhea, dietary counseling by a registered dietitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
(46 reference statements)
0
28
0
Order By: Relevance
“…Linoleic acid and linolenic acid are essential polyunsaturated fatty acids with anti-inflammatory properties. Proper intake of these polyunsaturated fatty acids plays an active role in improving kidney function in patients with DKD ( Garman et al, 2009 ; Mali et al, 2016 ; Dos Santos et al, 2018 ). However, it is shown that the levels of free fatty acids such as linoleic acid and arachidonic acid in the urine of patients with DKD are significantly increased ( Sasaki et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Linoleic acid and linolenic acid are essential polyunsaturated fatty acids with anti-inflammatory properties. Proper intake of these polyunsaturated fatty acids plays an active role in improving kidney function in patients with DKD ( Garman et al, 2009 ; Mali et al, 2016 ; Dos Santos et al, 2018 ). However, it is shown that the levels of free fatty acids such as linoleic acid and arachidonic acid in the urine of patients with DKD are significantly increased ( Sasaki et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is of interest to note that the 18:2 and 18:3 acyl chains, which are the sole precursors of other NEFAs [ 32 ], are essential fatty acids that cannot be synthesised by mammals [ 33 ]. Further, dietary studies report that an increased intake of NEFA 18:2 and 18:3 is negatively associated with DKD, which supports their importance in disease development [ 34 , 35 ]. One possible implication of the importance of NEFA 18:1, 18:2, and 18:3 and DG 18:2/18:2 is that they promote activation of protein kinase C (PKC) [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 90%
“…In fact, increased proteinuria, uncontrolled hypertension, and sustained high glucose levels in diabetes and dyslipidemia are well-known risk factors for CKD progression [ 40 , 41 , 42 , 43 ]. Many studies have reported the importance of dietary fat in CKD and CKD progression and have shown the association between dietary fat content and kidney function assessed by albuminuria or the GFR [ 33 , 34 , 35 ]. A lower intake of PUFAs, linoleic acid (LA, C18:2 n -6) and α-linolenic acid (ALA, 18:3 n -3), is related to CKD (24-h urinary albumin excretion of >30 mg and/or GFR of <60 mL/min/1.73 m 2 ) in patients with type 2 diabetes [ 33 , 34 ].…”
Section: Impact Of Dietary Fas On Ckd Risk Predictionmentioning
confidence: 99%
“…Many studies have reported the importance of dietary fat in CKD and CKD progression and have shown the association between dietary fat content and kidney function assessed by albuminuria or the GFR [ 33 , 34 , 35 ]. A lower intake of PUFAs, linoleic acid (LA, C18:2 n -6) and α-linolenic acid (ALA, 18:3 n -3), is related to CKD (24-h urinary albumin excretion of >30 mg and/or GFR of <60 mL/min/1.73 m 2 ) in patients with type 2 diabetes [ 33 , 34 ]. Significantly higher intake of PUFAs and lower intake of MUFAs were found in patients with diabetes and CKD than in patients without CKD in a cross-sectional study [ 34 ].…”
Section: Impact Of Dietary Fas On Ckd Risk Predictionmentioning
confidence: 99%
See 1 more Smart Citation